Normal values of regional and global myocardial wall motion in young and elderly individuals using navigator gated tissue phase mapping - Codreanu, Ion (Springer Netherlands, 2013)
The purpose of this study was to evaluate normal values for regional and global myocardial wall motion parameters in young and elderly individuals, as detected by navigator gated high temporal resolution tissue phase mapping. Radial, longitudinal and circumferential ventricular wall motion, as well as ventricular torsion and longitudinal strain rates, were assessed in two age groups of volunteers, 23 ± 3 (n = 14) and 66 ± 7 years old (n = 9), respectively. All subjects were healthy, non-smokers without known cardiac disease. An increased global left ventricular (LV) torsion rate (peak systolic torsion rate 20.6 ± 2.0 versus 14.5 ± 1.0°/s/cm, peak diastolic torsion rate −25.2 ± 1.8 versus −14.1 ± 1.3°/s/cm) and a decrease in longitudinal LV motion (peak systolic values at mid-ventricle 5.9 ± 0.5 versus 8.5 ± 0.8 cm/s, peak diastolic values −10.7 ± 0.7 versus −15.2 ± 0.9 cm/s) in the older age group were the most prominent findings. Lower peak diastolic radial velocities with a longer time-to-peak values, most pronounced at the apex, are consistent with reduced diastolic function with ageing. Lower peak clockwise and counter-clockwise velocities at all LV levels revealed limitations in resting LV rotational motions in the older group. Significant changes in the undulating pattern of the rotational motions of the left ventricle were also observed. The results demonstrate distinct changes in regional and global myocardial wall motion in elderly individuals. Increased LV torsion rate and reduced LV longitudinal motion were particularly prominent in the older group. These parameters may have a role in the assessment of global LV contractility and help differentiate age-related changes from cardiac disease.